Turning Coacervates into Biohybrid Glass: Core/Shell Capsules Formed by Silica Precipitation in Protein/Polysaccharide Scaffolds. Issue 39 (23rd July 2013) - Erni, Philipp; Dardelle, Gregory; Sillick, Matthew; Wong, Kenneth; Beaussoubre, Pascal; Fieber, Wolfgang
<x xml:space="preserve">Abstract</x> In case of emergency, break glass: Biohybrid core/shell capsules (see picture) suitable for encapsulation of volatile molecules can be formed through precipitation of amorphous silica in a protein/polyanion coacervate scaffold. The coacervate molds the final shape and structure of the capsule shell and provides an acidic microenvironment to locally induce hydrolysis and condensation of liquid silica precursors.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>